Reforming Juvenile Detention for Youth with Developmental Disabilities: I.T. v. Los Angeles County. (3rd July 2019) - Weinberg, Lois; Herz, Denise; Smith, Jolan; Chan, Kristine
Abstract: Alleged violations of disability laws regarding youth with developmental disabilities in juvenile detention led to a Settlement Agreement in I.T. v. Los Angeles County and subsequent reforms. Using multiple sources of data, this study shows high rates of compliance with screening timelines and the development of individual treatment and discharge plans. Multiagency staff found the reforms beneficial. Staff training proved not to have been adequate in some areas. The attorneys who negotiated the Agreement provided close oversight and monitoring.